CORRELATIVE STUDY BETWEEN STUDENTS’ ABILITY IN USING FOUR PARTS OF SPEECH AND THEIR ABILITY IN WRITING NARRATIVE PARAGRAPH FOR THE THIRD SEMESTER OF ENGLISH PROGRAM OF STKIP HAMZANWADI AT SELONG - Syamsul Rizal (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2018)
The problems of this study are to what extent is students’ ability in using four parts of speech for the third semester of English Program of STKIP Hamzanwadi at Selong, to what extent is students’ ability in writing narrative paragraph to use appropriate words form for the third semester of English Program of STKIP Hamzanwadi at Selong? And to what extent is correlation between students’ ability in using four parts of speech and their ability in writing narrative paragraph for the third semester of English Program of STKIP Hamzanwadi at Selong? In this study, the researcher took 40 students as the sample. Moreover, in collecting the data he used tests as the instrument. The data analysis, the researcher used inferential statistic research, while in hypothesis testing used formula of “r” technique. Based on the result of data analysis, it was known that the mean score (M) for students’ ability in using four parts of speech was 5.5 and the Standard Deviation (SD) was 5.85. It means that students’ ability in using four parts of speech of the third semester of English program was included average category rank and the mean score for students’ ability in writing narrative paragraph to use appropriate word forms of the third semester of English program was 4.33 and the standard deviation was 4.69. It means that students’ ability in writing narrative paragraph to use appropriate word form was included average category rank too. Furthermore, in testing hypothesis, it was known that rxy was 0.69 and r-table at 5% was 0.325 and at 1% was 0.418. It was concluded that the null hypothesis was rejected and the alternative hypothesis was accepted because rxy was higher than r-table. Based on the results of the data analysis and hypothesis testing, it could be known that there was positive correlation between students’ ability in using four parts of speech and their ability in writing narrative paragraph